2021
DOI: 10.3389/fmed.2021.626948
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Microarray Analyses in Hepatic Ischemia-Reperfusion Injury With Ischemic Preconditioning Prevention

Abstract: Ischemic preconditioning (IPC) represents an effective intervention to relieve hepatic ischemia-reperfusion injury (IRI). Systematic detection of circRNA expression revealing the protection effect of IPC still remains to be elucidated. Here, we applied a microarray to detect circRNA and mRNA expression in ischemic liver with and without IPC (n = 3 in each group). Compared with the sham group, there were 39 circRNAs and 432 mRNAs increased and 38 circRNAs and 254 mRNAs decreased (fold change ≥1.5, P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Interestingly, a recent study established a similarity of major mRNA involved in hepatic IRI during experimental and clinical settings. 47 Secondly, the ischemic preconditioning by using d-P initol cannot be considered as a routine treatment option for the hepatic infraction as this event is not preplanned thus, this preconditioning can utilize for controlled elective situations. Thirdly, although the d-P initol showed promising potential against warm IRI during hepatic transplant, these results cannot be extended to prevent organ damage during cold storage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study established a similarity of major mRNA involved in hepatic IRI during experimental and clinical settings. 47 Secondly, the ischemic preconditioning by using d-P initol cannot be considered as a routine treatment option for the hepatic infraction as this event is not preplanned thus, this preconditioning can utilize for controlled elective situations. Thirdly, although the d-P initol showed promising potential against warm IRI during hepatic transplant, these results cannot be extended to prevent organ damage during cold storage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IPO, IPC can attenuate HIRI. Tian et al[ 155 ] reported the circRNA profiles of mice with ischemic livers, with and without IPC. The data revealed that there were 77 circRNAs and 686 mRNAs in the IRI group, 50 circRNAs and 95 mRNAs in the IPC group (fold change ≥ 1.5, and P value < 0.05), respectively, when compared with those in the sham group.…”
Section: Circular Rnasmentioning
confidence: 99%
“…Ischemia/reperfusion kidney injury circAKT3 upregulated Promotes cell apoptosis [99] circ_001839 upregulated Promotes inflammatory response [100] circ_0023404 upregulated Promotes cell apoptosis and inflammatory response [101] Renal fibrosis circPlekha7 downregulated Promotes cell proliferation [104] Lupus nephritis circHLA-C upregulated Promotes lupus nephritis pathogenesis [106] Heart Myocardial ischemia-reperfusion injury circ_0030235 upregulated Promotes cell apoptosis [30] circ_0001206 downregulated Promotes cell apoptosis [109] circSAMD4A upregulated Promotes cell apoptosis and inflammatory response [110] circFOXO3 downregulated Inhibits inflammatory response [111] circRbms1 upregulated Promotes FOXO1 expression [112] circUBXN7 downregulated Inhibits cell apoptosis and inflammatory response [113] circPostn upregulated Promotes cell apoptosis [115] circHelz upregulated Promotes inflammatory response [116] Cardiac fibrosis circNFIB downregulated Promotes fibroblast proliferation and cardiac fibroblast-to-myofibroblasts differentiation [118] circRNA_000203 upregulated Promotes α-SMA, Col1a2 and CTGF expression [120] circHIPK3 upregulated Promotes α-SMA, Col1a1 and Col3a1 expression [121] Liver Hepatic fibrosis circPSD3 downregulated Promotes inflammatory response [123] circ_0067835 upregulated Promotes cell proliferation [125] Hepatic ischemia-reperfusion injury circRNA_017753 downregulated Activates Jade1 signalling pathway [129] Radiation-induced liver Injury hsa_circ_0071410 upregulated Promotes cell proliferation [131] circTUBD1 upregulated Promotes inflammatory response [133] circRSF1 upregulated Promotes cell proliferation and inflammatory response [136] Intestine Intestinal injury circRNA_Maml2 downregulated Promotes cell proliferation, differentiation and migration [28] circHIPK3 downregulated Inhibits cell proliferation [139] Reproductive system…”
Section: Types Of Injury Circrna Expression Pattern Downstream Regula...mentioning
confidence: 99%
“…Using hepatic artery occlusion-induced mice models, 43 significantly upregulated circRNAs and 7 significantly downregulated circRNAs were found in IPC-treated ischemic mice liver cells. Further analyses identified that circRNA_017753 exhibited sponging activities against miR-218-5p, miR-7002-3p and miR-7008-3p to regulate the Jade Family PHD Finger 1 (Jade1) signalling pathways [129]. Jade1, as a component of the HBO1 complex, was reported as a key regulator of cell cycle progression, redifferentiation and apoptosis [130].…”
Section: Hepatic Ischemia/reperfusion Injurymentioning
confidence: 99%